Factors influencing German house owners' preferences on energy retrofits - Martin Achtnicht; Reinhard Madlener (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
In this paper, we identify key drivers and barriers for the adoption of building energy retrofits in Germany, which is promoted by public policy as an important measure to address the future challenges of climate change and energy security. We analyze data from a 2009 survey of more than 400 owner-occupiers of single-family detached, semidetached, and row houses in Germany, that was conducted as a computer-assisted personal interview (CAPI). In the survey, respondents were asked directly for reasons for and against retrofitting their homes, but also faced a choice experiment involving different energy retrofit measures. Overall, both the descriptive and econometric results show that house owners who are able to afford it financially, for whom it is profitable, and for whom there is a favorable opportunity, are more likely to undertake energy retrofit activities. Based on an estimated mixed logit error component model, we also simulate the incentive effects of different policy options, such as public subsidies and energy tax increases.
Keywords: C25; D12; Q40; 330; Building energy retrofit; Choice experiment; Energy effciency; Residential buildings